Projeto de guichê de atendimento contextualizado pela Análise Ergonômica do Trabalho - Fontes, Andréa Regina Martins; Braatz, Daniel; Bertoncello, Dernival; Santos, Luciana de Mendonça; Menegon, Nilton Luiz (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper is based on the results obtained in the design process for furniture conceived to the Brazilian Post Office counter clerk, in an ampler Ergonomics analysis project of the service rendered in commercial counters. Considering the social construction perspective in the project, the resulting device articulates the ergonomics logics, security, engineering, operational advertising and the disclosing conflict of values and variables, which are expressed in the new counter service in terms of physical structure and use. The resulting design indicates the conflict between the sales clerk and the regular clerk, consequence of the dichotomy between the public service versus market competition in an operational reality. The new design has made the work organization flexible, leaving a higher degree of freedom for the worker, in its operative way. Keywords: Design Study; Activity Analysis; Integration between Ergonomics and Design.